Correlation of Iron Tablet (Fe) Consumption in Adolescent Pregnant Women with the Weight of a New Born - Septiana Dwi Wuryaningtyas (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Iron tablets have many benefits such as reducing the risk of death during bleeding, preventing anemia, and increasing nutritional intake in the fetus. Pregnant women with adolescence are at higher risk of anemia and death than pregnant women of sufficient age. One impact that occurs due to the low consumption of iron tablets in teenage pregnant women is babies born with conditions such as low birth weight, normal weight, and overweight babies born.Objectives: This study to analyze the correlation between iron consumption tablets of adolescent pregnant women with the weight of new born.Methods: This research is a quantitative study that uses secondary data in the form of data from the 2017 IDHS. There are 692 teenage pregnant female respondents with variable consumption of iron tablets and birth weight of babies. Data analysis in the study used the Chi-Square test.Results: Teenage pregnant women who consume iron tablets by 70.8% and those who do not consume 29.2%. The category of babies born mostly at the weight of normal-born babies is 84.8%. While the low infant weight category is 10.7% with a fairly high amount. Chi-Square statistical test results showed a p value of 0.019 (p = 0.019 <0.05) and the Contingency Coefficient showed a value of 0.107.Conclusions: There was correlation between consumption of iron tablets in adolescent pregnant women with the weight of new born with the category of low birth weight babies, babies born normally and more babies born in Indonesia.Keywords: Iron tablets (Fe), teenage pregnant women, the weight of new born